2020
DOI: 10.2147/ijn.s252505
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hollow Prussian Blue Nanospheres for Photothermal/Chemo-Synergistic Therapy</p>

Abstract: Background: The integration of NIR photothermal therapy and chemotherapy is considered as a promising technique for future cancer therapy. Hollow Prussian nanospheres have attracted much attention due to excellent near-infrared photothermal conversion effect and drug-loading capability within an empty cavity. However, to date, the hollow Prussian nanospheres have been prepared by a complex procedure or in organic media, and their shell thickness and size cannot be controlled. Thus, a simple and controllable ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…PB is well known as a safe photothermal agent in the treatment of tumor ( Fu et al, 2012 ; Lu et al, 2020 ). In our study, we fabricated Mn-based PB nanocatalysts to acquire enhanced synergetic effect of PTT and CDT under the guidance of MRI.…”
Section: Discussionmentioning
confidence: 99%
“…PB is well known as a safe photothermal agent in the treatment of tumor ( Fu et al, 2012 ; Lu et al, 2020 ). In our study, we fabricated Mn-based PB nanocatalysts to acquire enhanced synergetic effect of PTT and CDT under the guidance of MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al synthesized cubic, spherical, different sizes (~30–200 nm) and positively charged PBNPs by changing the rate of iron ions and adjusting the reaction time ( Figure 3 A) [ 15 ]. Lu et al prepared HPB nanospheres, which solved the problem that the shell thickness and size of PBNPs could not be controlled; they also studied in vitro and in vivo biological effects in detail [ 29 ]. Zhang et al synthesized HPBZs with internal cavities through a simple, Bi 3+ -assisted, template-free synthesis strategy ( Figure 3 B) [ 30 ].…”
Section: Crystal Structure Preparation and Characterization Of Pbnpsmentioning
confidence: 99%
“…Because of their unique structure, HPB nanospheres have a great drug load rate and NIR photothermal conversion efficiency. Lu et al substituted Fe 2 O 3 nanospheres for the conventional FeCl 3 precursor, and then PBNPs were built into HPB nanospheres through an interface reaction [ 29 ]. Changing the growth period and template size under appropriate water and ethanol ratios allowed us to regulate the shell thickness and size of HPB nanospheres.…”
Section: Application Of Enzyme Activity Of Pbnpsmentioning
confidence: 99%
“… 35 , 36 Studies have shown that hollow Prussian blue nanoparticles can effectively load chemotherapy drugs and be used for tumor-targeted thermochemotherapy. 37–42 In addition, Prussian blue nanoparticles have the potential to be highly effective drug carriers due to their stable structure, good stability and long blood circulation time. 43 , 44 …”
Section: Introductionmentioning
confidence: 99%